On a Class of Elliptic Problems and Its Application to Heat Transfer in Nonconvex Bodies (Journal of Computational Mathematics, 2021)
This work presents a procedure for constructing the solution to a class of problems with application to heat transfer processes in which the energy reemission is not negligible. Such problems are characterized by a Poisson equation subjected to certain nonlinear boundary conditions. The solution is constructed from a sequence whose elements may be obtained from a minimum principle. Some practical situations are presented.